From Ecological Footprint to Ecological Rent: An Economic Indicator for Resource Constraints - Kurt Kratena (Austrian Institute of Economic Research (WIFO), 2007)
This paper takes as its starting point a combination of a (monetary) input-output model with a national Ecological Footprint account for Germany in the spirit of Wiedmann et al. (2006). Footprint as well as biocapacity are dealt with at the industry level. Gross output of each industry and final demand for each industry can then be split into a share that can be reconciled with biocapacity and another share that corresponds to biocapacity overshooting. The Ecological Footprint concept is extended in this study by introducing the additional biophysically productive land necessary for sustaining the given level of economic activity. It is assumed that each industry had to rent the corresponding areas and to apply a given technology in order to make this additional land biophysically productive. This results in a new technology for each industry leading to an increase in costs and prices. The new price level is directly linked to the share of output that corresponds to biocapacity overshooting. Economic indicators can be derived by measuring the income difference brought about by the price increase. This difference corresponds to a Ricardian rent which is due to resource constraints on output growth.
Keywords: 330; input-output models; Ecological Footprint; Ricardian rent; Input-Output-Analyse; Umweltverträglichkeit; Komparativer Vorteil; Umweltmanagement; Umweltschutz